The Histological Changes of Bones and Lining Mucosa in the Middle and Inferior Turbinate in Chronic Rhinosinusitis - Ghorbani , Jahangir; Rezaei , Mitra; Roshani Zaferanlo , Amir Sam; Zandi , Afsoon; Karimi Galougahi , Mahboobeh (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2023)
Background: There is an association between osteitis and symptoms in chronic rhinosinusitis (CRS), but the exact clinical significance of osteitis is unclear. Most histological studies on osteitis of paranasal sinuses are limited to the ethmoid bone. Aim: The current study examined the histologic changes of mucosa and bone in the middle turbinate and sphenoid sinus for comparison. Methods: The current observational, cross-sectional study was conducted in a tertiary referral university hospital, from September 2017 to September 2021. Consecutive adult patients with chronic rhinosinusitis symptoms who underwent endoscopic sinus surgery were enrolled in the study. Histopathological evaluations for the existence and level of inflammation were performed by a blinded pathologist regarding the history and imaging results. SPSS (version 26) was used to analyze the data and other analyses. Results: Inflammatory changes of mucosa in the middle and inferior turbinates and sphenoid sinuses were more severe than inflammatory changes of bone in these areas (p values 0.006, 0.003, and 0.046, respectively). There was no significant difference in the prevalence of bone and mucosal inflammation between the patients with polyps and the ones without polyps. We did not observe a significant difference in the prevalence of osteitis between the primary and revision surgery nor between patients with asthma and without asthma. There was an association between the severity of inflammatory changes of mucosa with bone in the middle and inferior turbinates and sphenoid sinus (p values 0.007, 0.002, and 0.037, respectively). Conclusion: The present study indicates that chronic rhinosinusitis is not a disease that only involves mucosa. It is thus necessary to expand the boundaries of treatment beyond mere mucosa.